KOMUNIKASI AGAMA DAN BUDAYA (Studi atas Budaya Kompolan Sabellesen Berdhikir Tarekat Qadiriyah Naqshabandiyah di Bluto Sumenep Madura) - Ach Shodiqil Hafil (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
The study discusses the types of religious and cultural communication of Kompolan Sabellesen ritual implementing dhikir khataman Tarekat Qadiriyah Nashabandiyah, and how the people in Bluto village mean the values of sufistic proselytizing internalized in Kompolan Sabellesen. The research is a case study with qualitative approach based on anthropological study. The analysis uses the symbolic interpretative madzhab. The result of the study shows that Kompolan Sabellesen has a very important role in the dynamic life of people in Madura. The collaboration of religious and cultural teaching becomes one unity that influences the way how the people view their religion and socialize its religious teaching in the society. Kompolan Sebellesen is a communication medium of religion and culture packed in religious rite collaborated with cultural practices as a means of strengthening Islamic brotherhood to create harmonic and humanitarian society. Moreover, by contemplating dhikir khataman Tarekat Qadiriyah Naqshabandiyah in Kompolan Sabellesen, they feel positive energy that results peace and happiness. In order to get the blessing of sufistic values, they usually use pure water that has been recited some prayers to drink as the manifestation of sacredness in profanity. Thus, the existence of Kompolan Sabellesen should be maintained as mediation and meditation media in approaching the God by using sufistic values internalized in cultural rite.